2009
DOI: 10.1057/dev.2009.60
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes of Belonging: Migration, exclusion and transnational rights in the Mediterranean

Abstract: Rodanthi Tzanelli and Majid Yar examine Mediterranean and wider European policies on migration in light of their exclusionary and discriminatory tendencies. The current rhetoric and exclusionary practices are cementing of profoundly differentiated rights to live, work and belong. They argue that the outsider status of migrants from the global East and South is reproduced in Europe through a range of patriarchal, racialized and nationalist cultural discourses that strip away rights and consign migrants to polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, research has shown that even pro-migrant groups do not provide genuine agency for the people they claim to speak for; migrants largely remain voiceless in a volatile and increasingly brutalised discourse about their lives (Karatzogianni et al , 2016). In Italy and Greece, the dire economic situation had a tangible impact: on one hand, the migration crisis became a bargaining chip for countries that sought better conditions and outcomes in bailout negotiations; on the other hand, migration exerted further pressure on already strained social cohesion and solidarity, which resonated in discriminatory policies (Tzanelli and Yar, 2009). The unfolding and handling of the Eurozone crisis as well its connection to the migration crisis, and the capability of European politicians to find solutions to both, was frequently addressed in the online media discourse (EurActiv.com, 2015; Schick, 2016; Reuters, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, research has shown that even pro-migrant groups do not provide genuine agency for the people they claim to speak for; migrants largely remain voiceless in a volatile and increasingly brutalised discourse about their lives (Karatzogianni et al , 2016). In Italy and Greece, the dire economic situation had a tangible impact: on one hand, the migration crisis became a bargaining chip for countries that sought better conditions and outcomes in bailout negotiations; on the other hand, migration exerted further pressure on already strained social cohesion and solidarity, which resonated in discriminatory policies (Tzanelli and Yar, 2009). The unfolding and handling of the Eurozone crisis as well its connection to the migration crisis, and the capability of European politicians to find solutions to both, was frequently addressed in the online media discourse (EurActiv.com, 2015; Schick, 2016; Reuters, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%